Deciphering the role of cytidine triphosphate synthase (TgCTP) in the parasite Toxoplasma gondii (2015)
Toxoplasmosis is caused by the intracellular obligate parasite Toxoplasma gondii. The current treatments against toxoplasmosis display adverse reactions in many patients, thus, it is important to seek new targets for drug design. Cytidine triphosphate synthase (CTP synthase, EC 6.3.4.2) catalyzes the production of CTP from UTP, the final step in the production of cytidine nucleotides, and the first step in the formation of phospholipid intermediates. CTP synthases also play structural roles associated with maintaining cell shape in organisms such as Caulobacter crescentus. In most other organisms, including mammalian cells, the structural roles are unknown. We have identified and characterized the CTP synthase from T. gondii (TgCTP). Complementation of a lethal double mutant in S. cerevisiae by TgCTP was assessed using a plasmid shuffling approach. TgCTP permitted growth of S. cerevisiae on selective medium, indicating that the parasite protein was capable of substituting for the yeast proteins in vivo. We have also expressed and purified recombinant full-length and truncated his-tagged TgCTP proteins from Escherichia coli. Both TgCTP recombinant proteins were active and kinetic parameters were determined